2020
DOI: 10.1016/j.radcr.2019.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Twin pregnancy with metastatic complete molar pregnancy and coexisting live fetus

Abstract: We present a case of a 34-year old G1P0 female with twin-gestation and positive prenatal screening. Initial ultrasounds demonstrated a normal live fetus with an indeterminate but persistent placental lesion. The patient presented at 23 weeks of gestational age with vaginal bleeding. On examination, a 2 cm vaginal lesion was identified. Further cross-sectional imaging demonstrated a normal appearing fetus with a mixed solid and cystic placental lesion as well as an additional lesion in the vagina. Metastatic wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Sebire et al reported that only four cases of GTN occurring in 77 cases of CHMCF pregnancies (5.2%) required multidrug combination chemotherapy [ 5 ], suggesting CHMCF does not present a high risk for GTN. However, previous case reports describe diagnoses of high-risk GTN after CHMCF or cases requiring multidrug combination chemotherapy for GTN (presumed to be high-risk GTN) [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In six of 12 cases (50%), including the present case, single-agent chemotherapy was given as the initial chemotherapy for PTD.…”
Section: Discussionmentioning
confidence: 99%
“…Sebire et al reported that only four cases of GTN occurring in 77 cases of CHMCF pregnancies (5.2%) required multidrug combination chemotherapy [ 5 ], suggesting CHMCF does not present a high risk for GTN. However, previous case reports describe diagnoses of high-risk GTN after CHMCF or cases requiring multidrug combination chemotherapy for GTN (presumed to be high-risk GTN) [ [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ]. In six of 12 cases (50%), including the present case, single-agent chemotherapy was given as the initial chemotherapy for PTD.…”
Section: Discussionmentioning
confidence: 99%
“…Since the management of these two conditions differs, distinguishing between them is important. This is a rare phenomenon [7,10,11], and as a result, not many of us are acquainted with this condition. In cases of a partial hydatidiform mole, pregnancy termination is advised, as the fetus is chromosomally abnormal.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent advances in ultrasonography, CHMCF can even be incidentally detected starting late in the first trimester [103,108]. In this condition, the complete mole typically presents with a classical snowstorm appearance together with the presence of a normal placenta and a viable fetus [4,7,12,103,110]. Occasionally, a theca lutein cyst is detected on ultrasound due to a significantly elevated level of serum beta-hCG, suggesting a higher probability of CHMCF [45,103,109,111,112].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations